2007
DOI: 10.1590/s0034-72992007000400010
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre limiares de audibilidade e eletrofisiológico por estímulo tone burst

Abstract: Estudos referem compatibilidade entre limiares eletrofisiológicos obtidos com o estímulo acústico tone burst no Potencial Evocado Auditivo de Tronco Encefálico (PEATE) e limiares para tons puros. OBJETIVOS: Verificar a ocorrência das ondas I, III, V e seus respectivos tempos de latência para o tone burst em 500, 1000, 2000 e 4000 Hz a 80 dB NA, e comparar os limiares eletrofisiológicos para o tone burst com limiares de audibilidade e psicoacústico. CASUÍSTICA E MÉTODOS: Avaliação audiológica, psicoacústica e e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
3
9
0
7
Order By: Relevance
“…Similarities in the side or ears -as noted in the present study -have also been reported in the literature 7,[23][24][25] . In the complete series (n = 72 ears) the mean minimum response was 32.4 dBnHL (52.4 dBSPL) at 2 kHz for tone burst ABR in the term and preterm groups.…”
Section: Discussionsupporting
confidence: 91%
“…Similarities in the side or ears -as noted in the present study -have also been reported in the literature 7,[23][24][25] . In the complete series (n = 72 ears) the mean minimum response was 32.4 dBnHL (52.4 dBSPL) at 2 kHz for tone burst ABR in the term and preterm groups.…”
Section: Discussionsupporting
confidence: 91%
“…The latency extension can happen because of an increase in wave I latency as a result of an auditory loss on the high frequencies, not identified in the tonal audiometry from 250 to 8,000 Hz; however, the interpeaks are not very much affected in function of the hearing loss and, even in these cases, BAEP can be reliably used in order to establish the function involving the central auditory pathways 9 . One of the few studies concerning the lack of wave I was carried out with adult individuals who were audiologically normal and in whom we did not observe waves I and III at 80 dB HL in the frequencies of 500; 1,000; 2,000 and 4,000 Hz, in the BAEP with a tone burst stimulus 22 . The increase in absolute latencies with unaltered interpeak intervals is a common finding in conductive hearing loss 23,9 and it was also found in patients with Ménière 24 .…”
Section: Discussionmentioning
confidence: 72%
“…Investigações prévias [11][12][13] sugerem um aumento da latência com a diminuição do nível de intensidade, bem como uma diminuição da latência com o aumento da frequência avaliada.…”
Section: Frequency-specific Auditory Brainstem Response In Infants Wiunclassified